Bilingual Preschoolers' Speech is Associated with Non-Native Maternal Language Input. Issue 1 (2nd January 2019) - Stoehr, Antje; Benders, Titia; van Hell, Janet G.; Fikkert, Paula
ABSTRACT: Bilingual children are often exposed to non-native speech through their parents. Yet, little is known about the relation between bilingual preschoolers' speech production and their speech input. The present study investigated the production of voice onset time (VOT) by Dutch-German bilingual preschoolers and their sequential bilingual mothers. The findings reveal an association between maternal VOT and bilingual children's VOT in the heritage language German as well as in the majority language Dutch. By contrast, no input-production association was observed in the VOT production of monolingual German-speaking children and monolingual Dutch-speaking children. The results of this study provide the first empirical evidence that non-native and attrited maternal speech contributes to the often-observed linguistic differences between bilingual children and their monolingual peers.